Family Caregivers’ Perspective for Cancer Care in a Tertiary Care Centre of Assam - Marycharan Devi Sagolsem; Tulika Goswami Mahanta (Healthline, 2025)
Introduction: Family caregivers (FC) of patients with cancer has to undergo a lot of difficulties while taking care of the patients especially during advanced stage and often face burnout. Objective: To assess cancer patient’s caregivers’ perspective in a tertiary care centre of Dibrugarh, Assam. Methods: A Cross-sectional mixed method study was done among. Sample size was 180.  Patients with cancer and their primary caregivers in a Tertiary Cancer Centre of Assam were enrolled between May-November 2024. Pretested and predesigned questionnaire was used to collect data from caregivers of cancer patients. Zarit Burden Interview (ZBI) format was used for assessing burden of caregivers.  In depth interview of 20 caregivers (till saturation level) was done and the data collected was used for qualitative study. Analysis was done using SPSS 25 and Atlas TI. Result: A total of 155 participated in the study. Mean age of the caregivers was 42.26 ± 11.84 years and mean Zarit Burden score of caregivers was 36.44±9.65. Majority (103, 67%) caregivers reported mild-to-moderate burden, while 41 caregivers (26%) reported moderate-to-severe burden. Financial constrain, lack of social and emotional support, communication challenges emerged as major themes in qualitative study. Conclusion: Financial and emotional strain, dependency, anxiety and stress need to be addressed with holistic implementation of community-based interventions such as different welfare scheme, strengthened support system and communication interventions.